1992
DOI: 10.1165/ajrcmb/7.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ICAM-1 Expression on Human Airway Epithelial Cells by Inflammatory Cytokines: Effects on Neutrophil-Epithelial Cell Adhesion

Abstract: Inflammation of the human airways in diseases such as chronic bronchitis, cystic fibrosis with Pseudomonas endobronchial infection, and possibly asthma during late-phase reactions involves a local influx of neutrophils (PMN) that may participate in airway epithelial injury. PMN-mediated cellular injury is most efficient under conditions of PMN-target cell adhesion. PMN express adhesive glycoproteins of the CD11/CD18 family that are counter-receptors for intercellular adhesion molecule-1 (ICAM-1), found on vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(167 citation statements)
references
References 32 publications
6
160
1
Order By: Relevance
“…PMN transepithelial migration can be viewed as a multi-step response that can be initiated by both host and pathogen derived stimuli such as IL-8 and N-formylated peptides respectively (Prossnitz & Ye 1997, Tavares-Murta et al 2002, Ramos et al 2003) From our studies and those of others (Parkos et al 1991, Tosi et al 1992, Agace et al 1995, it is clear that the β2 integrin CD11b/CD18 is central in regulating early adhesive events in the transepithelial migration response. PMN adhesion to epithelial monolayers can be blocked using monoclonal antibodies to CD11b, and furthermore, using specific antibodies in mapping studies, it was demonstrated that a domain consisting of 200 amino acids (I domain) is a major binding region for CD11b/CD18 ligands, including those on intestinal epithelial cells (Parkos et al 1991, Balsam et al 1998.…”
Section: The Molecular Basis Of Pmn Transepithelial Migrationmentioning
confidence: 56%
“…PMN transepithelial migration can be viewed as a multi-step response that can be initiated by both host and pathogen derived stimuli such as IL-8 and N-formylated peptides respectively (Prossnitz & Ye 1997, Tavares-Murta et al 2002, Ramos et al 2003) From our studies and those of others (Parkos et al 1991, Tosi et al 1992, Agace et al 1995, it is clear that the β2 integrin CD11b/CD18 is central in regulating early adhesive events in the transepithelial migration response. PMN adhesion to epithelial monolayers can be blocked using monoclonal antibodies to CD11b, and furthermore, using specific antibodies in mapping studies, it was demonstrated that a domain consisting of 200 amino acids (I domain) is a major binding region for CD11b/CD18 ligands, including those on intestinal epithelial cells (Parkos et al 1991, Balsam et al 1998.…”
Section: The Molecular Basis Of Pmn Transepithelial Migrationmentioning
confidence: 56%
“…[35][36][37] In addition, in vitro studies have shown that ICAM-1 expressed on lung epithelial cells is able to support neutrophil adhesion. 48 Taken together, the loss of ICAM-1 expression on alveolar type I and II epithelial cells and airway epithelial cells, as well as endothelial cells, could all contribute to the decreased level of inflammation and fibrosis observed in ICAM-1 Ϫ/Ϫ mice. In fact, alveolar epithelial ICAM-1 may bind and retain leukocytes within the alveolar spaces, resulting in direct epithelial injury and the sustained release of cytokines.…”
Section: Discussionmentioning
confidence: 94%
“…There are few data available at present concerning the induction of adhesion molecules by viral proteins. TOSI et al [18] showed that parainfluenza virus infection of human airway epithelium resulted in increased ICAM-1 expression [18]. In another study, HU et al [19] demonstrated that hepatitis-B virus Xprotein upregulates ICAM-1 transcription.…”
Section: Discussionmentioning
confidence: 99%